The use of high frequency waves to treat onychomycosis-preliminary communication of three cases - Silva, Juliana Leal Monteiro da; Doimo, Gabriela; Faria, Daniele Pedroso (Soc Brasileira Dermatologia, 2011)
The research evaluated the efficacy of high frequency waves in the treatment of onychomycosis in three patients during twelve months through the clinical examination of nails and also through mycological examination. The causative agent of the mycosis, in the three patients, was the dermatophyte Trichophyton rubrum and after application of high frequency, it was possible to notice a great improvement in the appearance of nails and also growth inhibition in culture despite the fact that the mycological examination remained positive. The preliminary study of the three cases demonstrated that the fungistatic activity of high frequency waves is a promising method to be used in combination with conventional drugs.
Uso de ondas de alta frequência no tratamento de onicomicose - comunicação preliminar de três casos
Keywords: Nails; Onychomycosis; Primary treatment